Desnutrición en los niños y niñas de la escuela de educación básica Juan Manuel Lasso - Tocte Toctaguano, Lidia Fabiola (2017)
Malnutrition has been a problem that has attracted a number of inconveniences in people because of the effort that has been carried out in this project whereby a student passing through Juan Manuel Lasso Educative School, it has observed this type of shortcomings in the subjects being one of the main problems in the teaching-learning process, this has at the same time generated an inadequate academic training for development in the social field, this project seeks to contribute in an effective way to the reduction of the food insecurity of the institution, At the same time you should reduce the rates of diseases associated with malnutrition. In order to achieve the objective of designing methodological strategies that promote an adequate food habit, avoiding malnutrition in children, not only within the institution but also outside it, the development of this strategy can strengthen the learning process and the At the same time, managers will be concerned with identifying students who are facing this problem, in the documents they are expected to look for in their classroom at the time of learning problems due to malnutrition. Take the awareness that a good diet generates health and this at the same time can generate the greatest performance in the learning process without any help without the help of the parents since of them it is expected that after proposing the Workshop development To improve the nutrition of children by eating healthy and healthy, the educational community put it into practice said in front of students these workshops help improve academic performance....